2021
DOI: 10.1186/s13075-021-02609-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity of IgM anti-modified protein antibodies in rheumatoid arthritis despite limited mutational load

Abstract: Background Anti-modified protein antibodies (AMPA) targeting citrullinated, acetylated and/or carbamylated self-antigens are hallmarks of rheumatoid arthritis (RA). Although AMPA-IgG cross-reactivity to multiple post-translational modifications (PTMs) is evident, it is unknown whether the first responding B cells, expressing IgM, display similar characteristics or if cross-reactivity is crucially dependent on somatic hypermutation (SHM). We now studied the reactivity of (germline) AMPA-IgM to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
4
8
0
Order By: Relevance
“…These results indicate that cross-reactivity towards different PTMs emerges when AMPA responses become detectable and provide evidence that cross-reactivity towards different PTMs is an intrinsic characteristic of AMPA responses. This finding is in line with the observation that (germline) ACPA-IgM can be cross-reactive towards other PTMs as well 6. Although cross-reactivity seems to be an intrinsic feature of AMPA, it is tempting to speculate that the most cross-reactive B cells are selected during progression towards RA, explaining the increase of the ACPA epitope recognition profile in time towards disease onset.…”
supporting
confidence: 85%
“…These results indicate that cross-reactivity towards different PTMs emerges when AMPA responses become detectable and provide evidence that cross-reactivity towards different PTMs is an intrinsic characteristic of AMPA responses. This finding is in line with the observation that (germline) ACPA-IgM can be cross-reactive towards other PTMs as well 6. Although cross-reactivity seems to be an intrinsic feature of AMPA, it is tempting to speculate that the most cross-reactive B cells are selected during progression towards RA, explaining the increase of the ACPA epitope recognition profile in time towards disease onset.…”
supporting
confidence: 85%
“…Thus, it is possible that the immune system generates “ACPA natural autoantibodies” that subsequently undergo T cell-promoted affinity maturation. In line with this, it has been reported that patient-derived, pentameric IgM ACPAs bind to a variety of post-translationally modified self-antigens, including citAgs, and that these properties are conserved within their germline ancestry 55 . Transgenic mice expressing IgM natural antibodies 56 , or mice injected with anti-dsDNA IgM antibodies 57 , were protected from nephritic damage in spontaneous models of lupus.…”
Section: Discussionmentioning
confidence: 65%
“…This class of antibodies binds autoantigens and consequently affects its functions or leads to cell elimination [ 26 ]. Several recent studies have demonstrated that autoreactive IgM can be causative for autoimmune symptoms as anti-BP180 IgM leads to IgM pemphigoid [ 65 ], anti-PT IgM antibodies interfere with blood coagulation in severe COVID-19 patients [ 51 , 78 ], or AMPA-IgM as disease driver in RA [ 73 ]. In conclusion, these studies and others indicate that autoreactive IgM is capable of causing autoimmune diseases in the absence of IgG autoantibodies ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether AMPA IgG require excessive somatic hypermutation (SHM) in order to bind modified proteins in a cross-reactive manner has been debated intensely. Interestingly, Reijm et al [ 73 ] have suggested that AMPA IgG might originate from AMPA IgM possessing germline configuration. The authors further show that AMPA IgM detected in RA patients can readily bind modified self-proteins and thus induce pathology.…”
Section: Autoreactive Igm: First Step In Establishing Autoimmune Dise...mentioning
confidence: 99%